Variations in the Aerosol Optical Depth above the European Russia Territory from the Data Obtained at the Russian Actinometric Network in 1976a2016 Years (Global Journal of Science Frontier Research, 2018)
Investigation results of the atmospheric aerosol over the Russia territory are of great interest for the ecology and climate developments. The regularities of spatial and temporal variations in the Aerosol Optical Depth (AOD) can be received by the Russian actinometric network data (Russian Hydrometeorological Research Center). Our analysis will be based on the "Atmosphere Transparency" special-purpose database created at the Voeikov Main Geophysical Observatory on the basis of observational actinometric data. Author has many years cooperation with MGO in the region of the processing and analysis of these observation data.